The Art in Medicine - Treatment Decision-Making and Personalizing Care: A Grounded Theory of Physicians' Treatment-Decision Making Process with Their (Stage II, Stage IIIA and Stage IIIB) Non-Small Cell Lung Cancer Patients in Ontario - Akram, Saira (My University, 2012)
Introduction: In Ontario alone, an estimated 6,700 people (3,000 women; 3,700 men) will die of lung cancer in 2011 (Canadian Cancer Society, 2011). A diagnosis of cancer is associated with complex decisions; the array of choices of cancer treatments brings about hope, but also anxiety over which treatment is best suited for the individual patient (Blank, Graves, Sepucha et al., 2006). The overall cancer experience depends on the quality of this decision (Blank et al., 2006). Clinical practice guidelines are knowledge translation tools to facilitate treatment decision-making. In Ontario, guidelines have been developed and disseminated with the purpose to inform clinical decisions, improve evidence based practice, and to reduce unwanted practice variation in the province. But has this been achieved? To study this issue, the purpose of the current study was to gain an in-depth understanding and develop a theoretical framework of how Ontario physicians are making treatment decisions with their non-small cell lung cancer patients. The following research questions guided the study: (a) How do physicians make treatment decisions with their stage II, stage IIIA and stage IIIB non-small cell lung cancer patients in Ontario? (b) How do knowledge translation tools, such as Cancer Care Ontario guidelines, influence the decision-making process?
Methods: A qualitative approach of grounded theory, following a social constructivist paradigm outlined by Kathy Charmaz (2006), was used in this study. 21 semi-structured interviews were conducted; 16 interviews with physicians and 5 with health care administrators. The method of analysis integrated grounded theory philosophy to identify the treatment decision-making process in non-small cell lung cancer, from the physician perspective.
Findings: The theory depicts the treatment decision-making process to involve five key “guides” (or factors) to inform the treatment-decision making process: the unique patient, the unique physician, the family, the clinical team, and the clinical evidence.
Conclusion: Decision-making roles in lung cancer are complex and nuanced. The use of evidence, such as, clinical practice guidelines, is one of many considerations. Information from a large number of sources and a wide array of factors, people, emotions, preferences, clinical expertise, experiences, and clinical evidence informs the dynamic process of treatment decision-making. This theory of the treatment decision-making process (from the physician perspective) has implications relevant to treatment decision-making research, theory development, and guideline development for non-small cell lung cancer.
Keywords: decision-making; lung cancer; lung neoplasm; cancer; conceptual models; treatment selection; and physician-patient interaction; clinical practice guideline; physicians’ practice patterns; guidelines; guidelines in use; guideline adherence; and guideline implementation; Clinical Epidemiology; Health Services Research; Knowledge Translation; Oncology; Clinical Epidemiology